Post-traumatic Intraocular Leiomyosarcoma in a Domestic Bovine Calf (Bos primigenius taurus). (April 2019) - Kleinschmidt, S.; Mammen, S.; Puff, C.
Summary: The present report describes a case of a post-traumatic ocular leiomyosarcoma in a calf ( Bos primigenius taurus ) including clinical, histopathological and immunohistochemical features. Following a traumatic episode, the animal developed opacification of the lens and shrinkage of the eye. Subsequently, the ocular lesion increased in size over a period of 6 weeks and reached up to 16 cm in diameter with infiltration into the cranium. At necropsy examination, the kidneys, liver and spleen exhibited multiple firm white metastases up to 2 cm in diameter. The mass was composed of closely-packed streams and bundles of neoplastic cells, which immunohistochemically expressed vimentin and alpha smooth muscle actin. Based on the anamnestic data, morphological appearance, distribution and immunohistochemical results, a diagnosis of a post-traumatic intraocular leiomyosarcoma was made. The tumour may have originated from cells lining the pectinate ligament of the ciliary body.